2022
DOI: 10.33549/physiolres.934995
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging on Mitochondrial Respiration in Various Organs

Abstract: Mitochondria are considered central regulator of the aging process; however, majority of studies dealing with the impact of age on mitochondrial oxygen consumption focused on skeletal muscle concluding (although not uniformly) a general declining trend with advancing age. In addition, gender related differences in mitochondrial respiration have not been satisfactorily described yet. The aim of the present study was to evaluate mitochondrial oxygen consumption in various organs of aging male and female Fischer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Using a similar OXPHOS antibody cocktail as in the present study, one study reported lower protein content of Complex I subunit NDUFB8 and Complex IV subunit II MTCO2 in normally aging mice, but significantly greater level of Complex V subunit ATP synthase subunit alpha and no changes to Complex II subunit 30 kDa SDHB or Complex III subunit Core 2 UQCRC2 [56] . Lower levels of subunits that form ETC Complexes I and IV complement other data reporting lower enzyme activity of those complexes [57] , [58] , [59] , [60] . Mindful that contributions of Complexes I and IV may be especially consequential to brain aging, it bears mention that analyzing associations of blood glucose with OXPHOS subunits separately within age groups reduced the significance of all associations whereas the effect sizes of NDUFB8 and MTCO1 were largely unaffected, continuing to reflect medium-sized effects (i.e., r > 0.4) for both proteins in either age group.…”
Section: Discussionsupporting
confidence: 83%
“…Using a similar OXPHOS antibody cocktail as in the present study, one study reported lower protein content of Complex I subunit NDUFB8 and Complex IV subunit II MTCO2 in normally aging mice, but significantly greater level of Complex V subunit ATP synthase subunit alpha and no changes to Complex II subunit 30 kDa SDHB or Complex III subunit Core 2 UQCRC2 [56] . Lower levels of subunits that form ETC Complexes I and IV complement other data reporting lower enzyme activity of those complexes [57] , [58] , [59] , [60] . Mindful that contributions of Complexes I and IV may be especially consequential to brain aging, it bears mention that analyzing associations of blood glucose with OXPHOS subunits separately within age groups reduced the significance of all associations whereas the effect sizes of NDUFB8 and MTCO1 were largely unaffected, continuing to reflect medium-sized effects (i.e., r > 0.4) for both proteins in either age group.…”
Section: Discussionsupporting
confidence: 83%
“…The sample size in the present study was 308, and the linear regression models allowed, in addition to examining the strength of the correlations, a quantification of the age effect. In a recent animal study with a large sample size, there was no decline in platelet respiratory function with age in 344 rats, even though such changes were seen in mitochondria from skeletal muscle and kidney cortex from the same rats 34 . We share the authors’ conclusion in that publication, further supported by the present findings, that one should be cautious not to generalize mitochondrial function across tissues.…”
Section: Discussionmentioning
confidence: 88%
“…Age dependence of mitochondrial function in various organs and brain regions in rats has been described [ 65 , 66 , 67 ]; the results did not confirm the concept of a general pattern of age-dependent mitochondrial dysfunction. No such data are available in humans; measurements in humans are usually performed using skeletal muscle biopsies, fibroblasts, and circulating blood cells [ 68 ].…”
Section: Introductionmentioning
confidence: 81%